2014
DOI: 10.1111/jan.12467
|View full text |Cite
|
Sign up to set email alerts
|

Exploring selection and recruitment processes for newly qualified nurses: a sequential‐explanatory mixed‐method study

Abstract: Most providers had processes which addressed the issue of quality in the selection and recruitment of newly qualified nurses. The 'assessment centre model', which providers were adopting, allowed for multiple levels of assessment and streamlined recruitment. There is a need to validate the efficacy of the selection tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…All studies except Newton et al . () included participants that were either service users or their family member. All except Dysvik et al .…”
Section: Resultsmentioning
confidence: 99%
“…All studies except Newton et al . () included participants that were either service users or their family member. All except Dysvik et al .…”
Section: Resultsmentioning
confidence: 99%
“…There should be an emphasis on the use of multiple methods in selecting and recruiting potential nursing students with appropriate values, attitudes and behaviour (Newton et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reasons for the lower quality assessment related to lack of reporting or regard for crucial elements of an MMR design. The most frequently used design was an explanatory sequential MMR design, whereby quantitative methods were followed by qualitative strands (e.g., Newton, Chandler, Morris‐Thomson, Sayer, & Burke, 2015). Those that justified this approach, such as Alabdulaziz, Moss, and Copnell (2017) and Halpin, Terry, and Curzio (2017), indicated that the intention of using this design was to enable a deeper understanding of the research topic through the use of qualitative approaches to enrich and explain the quantitative results.…”
Section: Resultsmentioning
confidence: 99%